Push-Pull Factors and Financial Inclusion of MSME Owners in Nigeria: An Empirical Analysis - Abdullahi Adio Babatunde; Ahmed Oluwatobi Adekunle (Universitas Islam Nahdlatul Ulama Jepara, 2025)
Objective: This study examines the determinants of financial inclusion among MSME owners in North Central Nigeria. Research Design & Methods: The study adopted a survey research design; the target population consisted of 11,607 MSME owners across North Central Nigeria. A combination of stratified and simple random sampling techniques was used to select participants. The sample size of 435 was determined using Krejcie and Morgan’s (1970) sample size formula. Data was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings: The findings revealed that push-pull factors significantly explained variations in financial inclusion. Based on these results, the study concludes that push-pull factors have a positive effect on the financial inclusion of MSME owners in North Central Nigeria. Practical Implications: This study accentuates the imperative for financial regulatory bodies to adopt targeted financial inclusion management strategies tailored to the unique needs of Micro, Small, and Medium Enterprises (MSMEs). By doing so, these institutions can catalyze economic emancipation, particularly in emerging economies such as Nigeria. Recommendations: The study recommends that the government should implement financial literacy programs to raise awareness among MSME owners about the importance of financial knowledge and skills. Additionally, the government should collaborate with banks to provide lower interest rates and more flexible repayment options to ensure that financial support effectively reaches the intended beneficiaries. Contribution & Value Added: This research contributes to the literature by empirically demonstrating the influence of push-pull factors such as necessity-driven entrepreneurship (push) and opportunity-driven entrepreneurship (pull) on MSME performance in Kwara State, Nigeria.